Penyuluhan Legalitas dan Perlindungan Hukum dalam Bisnis Digital - Jaya, Mahendra; Tejo Sasongko, Agus Eko; Umar, Ismail; Sutrisno, Edy; Desanti, Novi; Rinaldi, Hasymi; Anggita , Anggita (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
The digital economy encompasses online business transactions, electronic commerce, digital services, and the digital creative industry, offering opportunities for growth, innovation, and efficiency while also challenging privacy, data security, and the digital divide. Alumni have significant potential in the digital business world, with access to education, experience, and extensive networks. Some findings suggest that electronic money positively impacts economic growth, but legal protection challenges remain, such as consumer data breaches and the need for regulation. The PKM team provides outreach to alumni and active students on legal developments in digital business. Lectures and training methods are used to impart understanding of legality and legal protection in digital business. This outreach successfully enhances participants' understanding of legal aspects, such as business identification numbers (NIB), business permits, tax obligations, trademark registration, copyright, product regulations, and intellectual property protection to avoid legal risks and enhance their business reputation.